How to be an academic superhero: establishing and sustaining a successful career in the social sciences, arts and humanities - Hay, Iain (Edward Elgar Publishing, 2017)
In universities across the world, academics struggle to establish and sustain their careers while satisfying intensifying institutional demands. Drawing from the author's decades of observation and experience in academia, this exceptional book responds to the challenges of fostering a successful academic career. Featuring an overarching focus on holistic career development as well as specific chapters on mentorship, networking, job applications and interviews, publishing, funding and more, this book guides readers through their prospective academic careers while offering informed and compassionate advice and insights. While the book is organized chronologically, providing early-, mid- and late-career guidance, the issues and challenges discussed can be addressed continuously and sometimes simultaneously across an academic's professional life. In a straightforward and engaging style, How to be an Academic Superhero offers realistic, practical advice for anyone contemplating or developing an academic career in the social sciences, arts or humanities. Career mentors looking for a useful and accessible instructional resource will also find it to be of value